CHALLENGES OF TURNING AGRICULTURAL ECONOMIC TO HOUSEHOLD INDUSTRIES : HOW INDONESIA POSITION FACING ASEAN COMMUNITY 2015? - -, Winarti (PROCEEDING INTERNASIONAL SEMINAR, 2015)
Indonesia, known as an agricultural country, is marked by the majority of people living in village/ rural whose daily working is as farmer. To the year of 2005, there has been about 17,9 million agricultural workfield within the broad area of 15,4 million land where the usage of the land employed was about 0,7 hectare. This phenomenon shows such a decrease in the land ownership. This changing phenomenon of land ownership, creates a problem on working opportunity, since it has been any limitation on the widespread of workforce.This condition impacts on the changes within Javaâs rurals which leads to the unsufficiency of employment in the agricultural sectore. Such alternative should be considered, by promoting city mobility program, by taking the other industrial activities which stands to be their major expectation. On the other sides, the home industries are commonly recognized by the rurals. The rurals then start to be introduced about the small scale market economy. This strategy benefits the rurals in terms of providing a chance for their products (rural product) to be sold.Compared with the other countries in ASEAN Community position Indonesia were complexity problem. Exspeciale population growth Â± 1,9 percent. Until 2015, Indonesia population about 250 milion, mayority (Â± 68percent) living in village as a farmer. Their income percapita under us 1000.Key Words : Rural, Liberalism Household Industries